'It is a hard decision': a qualitative study of perinatal intimate partner violence disclosure - Malikeh Amel Barez; Khadijeh Mirzaii Najmabadi; Robab Latifnejad Roudsari; Mojtaba Mousavi Bazaz; Raheleh Babazadeh (BMC, 2022)
Plain language summary Disclosure of perinatal intimate partner violence is a difficult decision. Several barriers prevent abused pregnant women from disclosing violence. The present study explained barriers and facilitators of perinatal intimate partner violence disclosure. 23 women (11 pregnant and 12 after birth) who experienced perinatal intimate partner violence were interviewed in Mashhad, Iran. The results showed the barriers to disclosure include negative disclosure consequences and protection of family privacy and the facilitators of disclosure include maternal self-efficacy, threats to security, and formal and informal supportive networks. In conclusion eliminating barriers and strengthen facilitators play an important role in providing effective supportive services for abused women and reducing perinatal violence. The result will be useful to policymakers, health program planners, and health care providers for appropriate management of perinatal intimate partner violence.